Effect of subconcussive impacts on functional outcomes over a single collegiate football season. (December 2020) - Walter, Alexa E; Scaramuzzo, Madeleine; Bream, Tim; Seidenberg, Peter; Lynch, Scott; Slobounov, Semyon M
Context: In collision sports, particularly American football, athletes can accumulate thousands of subconcussive impacts, or head acceleration events (HAEs), across a single season; however, the short-term consequences of these impacts are not well understood. Objective: To investigate the effects of the accumulation of impacts during practices on cognitive functions over a single football season. Design: Prospective observational study. Setting: Athletic training room and University laboratory. Participants: Twenty-three NCAA Football Bowl Subdivision players. Main outcome measures: Helmet accelerometers during practices and virtual reality testing (VR; balance, reaction time, spatial memory) before and after the season. Results: Preseason had the majority of ≥80 G impacts while during the season had the majority of ≥25 G to <80 G impacts and positional differences showed that linemen had the majority of both types. Virtual reality analysis revealed that scores significantly decreased after the season for spatial navigation ( p  < 0.05) but not for balance or reaction time. Significant correlations ( p <  0.05) were found between cognitive measures and player demographic variables. Conclusions: Even in the absence of clinical symptoms and concussion diagnosis, repetitive impacts may cause cognitive alterations. Documenting the distribution of impact quantity and intensity as a function of time and position may be considered by coaches and clinicians to reduce the accumulation of impacts in athletes exposed in contact sports.